2019
DOI: 10.3390/ijerph16193735
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Pregnancy BMI Influences the Association of Dietary Quality and Gestational Weight Gain: The SECOST Study

Abstract: Poor diet quality in pregnancy could impact gestational weight gain (GWG) and consequently fetal growth and development. But today there is limited data available on gestational diet quality. This study investigated the association between diet quality in each pregnancy trimester and GWG in Malaysian women. Diet quality was assessed using the modified Healthy Eating Index for Malaysians (HEI). Total GWG was defined as the difference between measured weight at last prenatal visit and pre-pregnancy weight. About… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 50 publications
2
22
2
Order By: Relevance
“…Furthermore, only increased prepregnancy BMI was significantly associated with weight at delivery, AFI, glucose levels after delivery and menarche. This is to the certain degree in line with previous reports, where women with increased prepregnancy BMI tend to gain weight [ 28 , 29 ]. In the study of Dong et al, elevated prepregnancy BMI and excessive GWG in first trimester of pregnancy were associated with gestational DM [ 30 ]; however, Yong et al, reported that GWG nor in the first neither in the second trimester of pregnancy was independently associated with the risk for gestational DM [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, only increased prepregnancy BMI was significantly associated with weight at delivery, AFI, glucose levels after delivery and menarche. This is to the certain degree in line with previous reports, where women with increased prepregnancy BMI tend to gain weight [ 28 , 29 ]. In the study of Dong et al, elevated prepregnancy BMI and excessive GWG in first trimester of pregnancy were associated with gestational DM [ 30 ]; however, Yong et al, reported that GWG nor in the first neither in the second trimester of pregnancy was independently associated with the risk for gestational DM [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…The association between food security and diet quality was also documented in women with children [ 51 , 52 , 53 , 67 ]. The only study that reported on pregnant women found lower M-HEI scores throughout their pregnancy (ranging between 52.7–56.1%) [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…None of the reported studies explored the impact of diet quality on clinical outcomes in children, adolescents, young adults, or adult men ( Table 6 ). Limited evidence pointed toward positive associations between good diet quality and higher serum hemoglobin [ 64 ] and excessive gestational weight gain [ 54 ] in women. A negative association between diet quality and breast cancer risk was reported by one study [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fruit and vegetable consumption was not linked to GWG in other prospective studies ( 31 , 33 ). Although our study did not evaluate diet quality specifically, high fruit and vegetable consumption is consistently associated with higher diet quality ( 35 ); and diet quality has been linked with reduced GWG in several ( 32 , 36 38 ), but not all ( 39 41 ) prior studies. The underlying cause of these discrepancies between fruit/vegetable consumption or diet quality and GWG is unclear.…”
Section: Discussionmentioning
confidence: 89%